Export scope and characteristics of destination countries: Evidence from German transaction data - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2019)
This paper uses information on export transactions by German firms from 2011 to document the role of characteristics of destination countries for export scope, where export scope is defined as the number of different products a firm exports to a destination market. It demonstrates that in line with theoretical hypotheses intra-firm differences in export scope across destination countries are related to differences in the distance between Germany and the countries of destination, differences in the economic size and the per capita income of these countries, and in the ease of doing international trade with the countries.
Keywords: F14; 330; Export Scope; Transaction level data; Germany